THE IMPACT OF TRAINING BASED UPON MERITS IN IMPROVING THE EMPLOYEES PERFORMANCE AT THE JORDANIAN UNIVERSITY HOSPITALS Abstract - العزام انور احمد; مهدي لينا فؤاد (Journal of Economics and Administrative Sciences, 2018)
The study aims to identify the impact of competency-based training in its dimensions (skills, cognitive abilities, attitudes, and attitudes) in improving the performance of employees (achievement, strategic thinking and problem solving) in Jordanian university hospitals. The study based on analytical descriptive method. The study population consisted of the Jordanian University Hospitals, the University Hospital of Jordan and the King Abdullah Hospital, as applied study case. The sample of the study consists of all upper and middle administrative employees of these hospitals; questionnaire distributed all of them and the number of valid questionnaires for analysis were 182 questionnaire. The results showed that the independent variables (skills, diagnosis of attitudes, trends) have a statistically significant effect on improving the performance of workers in Jordanian hospitals, in light of the results study recommended increasing the efficiency of hospital staff and develop their skills through specialized training programs to improve their performance. The study also recommended rehabilitation of hospitals leaders with the ability to anticipate future events and the interaction of different visions in line with the environment challenge faced effectively.